Conjugated molecules for colourimetric and fluorimetric sensing of sodium and potassium. (25th June 2020) - Parr, Zachary S.; Nielsen, Christian B.
Abstract : New alkali metal ion sensors showing ratiometric colourimetric and fluorimetric responses with high selectivity and low limits of detection. Abstract : We present a series of conjugated molecules for colourimetric and fluorimetric sensing of alkali metal cations Na + and K + . The dye molecules are based on an electron-rich bithiophene core bridged by an oligoethylene glycol bridge capable of selectively binding either sodium or potassium. The molecules are further functionalised with electron-rich or electron-deficient moieties to modulate the band gap and thus shift the absorbance across the visible range. We observe distinct colour changes and high selectivity for alkali metal cations at millimolar concentrations. We moreover see highly selective fluorimetric responses with the molecules exhibiting either turn-on, turn-off or ratiometric sensing behaviour. We finally demonstrate a dual optical sensor capable of distinguishing between sodium and potassium in solution.